A PSO algorithm for constrained redundancy allocation in multi-state systems with bridge topology - Wang, Yong; Li, Lin (Computers & industrial engineering, 2014)
•A novel method for redundancy allocation for multi-state systems with bridge topology.•Utilize particle swarm optimization.•Capable of minimizing the system cost while satisfying required system availability.•Capable of maximizing the system availability with a limited budget. Bridge topology is a commonly used structure for load balancing and control in applications such as electric power generation and transmission, transportation and computer networks, and electronic circuits. The reliability performance of engineering systems with bridge topology can be characterized by multi-state models and enhanced by allocating redundant elements. The redundancy allocation problem, which aims at finding the optimal trade-off between system performance and investment costs, is proved difficult to solve and has received much attention in the literature. This paper advances a meta-heuristic approach called particle swarm optimization and applies it to effectively solve for near-optimal solutions to the redundancy allocation problem of multi-state systems with bridge topology. Two typical redundancy allocation problem formulations, i.e., minimizing the system cost while satisfying required system availability and maximizing the system availability with a limited budget, are studied. Heterogeneous redundancy, i.e., the mixture of redundant element types in each subsystem, is allowed in the formulations. The effectiveness and efficiency of the proposed approach are validated by the case studies of a bridge-structured coal conveyor multi-state system with extra constraints. The research results have practical meaning to the design and improvement of engineering systems with bridge topology.